Determination Of Self-Identity Construction Through Integration Of Self-Identity Theory And Adventure Tourism: A Case Study Of Surfing Activities On The South Coast Of Java - Nurdina Prasetyo; Pranoto Pranoto; Sukrisno Sukrisno; Idah Kusuna Dewi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research explores the role of self-identity in motivating young Indonesian tourists to participate in adventure tourism, specifically learning to surf on the southern coast of Java. Using a qualitative approach with two-phase interviews, this study involved participants from diverse cultural backgrounds who took surfing lessons at Menganti Beach, Widarapayung, and Parangtritis. Data analysis identified five key constructs influencing attitudes and participation intentions: novelty-seeking, connection to "sporty" and "surfer" identities, perceived mastery of the activity, and social value of the experience. The results indicate that surfing is viewed as a means of expressing and developing self-identity, with social aspects and the role of surf instructors emerging as significant factors. This research reinforces self-identity theory in the context of adventure tourism consumer behavior in Indonesia, providing valuable insights for developing more effective marketing strategies and tourism experiences. Practical implications include the development of tourism products that align with young tourists' self-identity, while theoretical implications encompass the expansion of self-identity theory application in the context of adventure tourism in developing countries.